Images of Organization - Gareth Morgan (USA Sage Publications, 2006)
Morgan shows managers how to break free of management fads by understanding the strengths and weaknesses of management metaphors and applying them to organizational life.
Keywords: Organization; Organizational behavior; Nonfiction; Business; Economics; Leadership; HRM: Contemporary Issues (HRM2074-N )